지향성 안테나 기반 전술 항공 네트워크를 위한 효율적인 토폴로지 제어기법 개발 및 성능분석 - 이성원 (The Graduate School, Ajou University, 2009)
Network Centric Warfare(NCW) is becoming a prominent concept in the current trend of warfare. To support high quality communication between strategic or tactical units, Air Backbone Networks(ABN) will be constructed in the near future to take part in the NCW. The ABN may be constructed as the part of 2-Tier airborne networks, which is proposed by U.S army, and will be similar with a wireless mesh network. The ABN has dynamic variations in its topology so that efficient and reliable neighbor discovery protocol and robust and well-connected topology control are needed for coping with these high mobility environments. The aircrafts constructing the ABN tends to have high dynamic mobility, causing frequent topology variations. This makes the research on reliable neighbor discovery an important factor in mobility management. However, the majority of the research pre-assumes a reliable neighbor discovery process so that every node can get the location information about nearby nodes and rarely consider the use of directional antennas. This paper presents the Adaptive HELLO Message Scheduling algorithm for reliable and efficient mobility management and the Distributed Web-Topology Control algorithm for robust and well-connected network in ABN, using directional antennas. The performance and effectiveness is evaluated through mathematical analysis and simulation experiments via the QualNet simulator.
학위논문(석사)--아주대학교 정보통신전문대학원 :정보통신공학과,2009. 2
Keywords: Topology Control; Neighbor Discovery; Airborne Network; Directional Antenna